2022
DOI: 10.1007/s10671-022-09312-5
|View full text |Cite
|
Sign up to set email alerts
|

Playful maths! The influence of play-based learning on academic performance of Palestinian primary school children

Abstract: This study explores the relationship between play-based learning and achievement in mathematics in Palestinian elementary school children. Forty teachers from eight schools received training in play-based pedagogies and follow-up support visits from programme staff (intervention group); four matched schools served as the control group. Grade-appropriate tests were administered to all students in two consecutive school terms. A total of 859 students (458 females, 401 males) and 832 students (477 females, 355 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…While much of the research on play-based approaches has taken place in the U.S., Europe and Australia, Hammad and AlShaer [16] noted that Palestinian students' low achievement in certain subjects may be enhanced by introducing play-based learning in Mathematics' and Arabic language subjects. Recently the positive relationship between play-based learning and test scores in Mathematics has been demonstrated for Palestinian elementary school children [27].…”
Section: Introduction 1value Of Play-based Learningmentioning
confidence: 99%
“…While much of the research on play-based approaches has taken place in the U.S., Europe and Australia, Hammad and AlShaer [16] noted that Palestinian students' low achievement in certain subjects may be enhanced by introducing play-based learning in Mathematics' and Arabic language subjects. Recently the positive relationship between play-based learning and test scores in Mathematics has been demonstrated for Palestinian elementary school children [27].…”
Section: Introduction 1value Of Play-based Learningmentioning
confidence: 99%
“…Researchers also agree that, on the physical level, children need to engage in play activities that facilitate both gross and fine motor development (Gashaj et al 2021). Quite recently, Murtagh, Sawalma and Martin (2020) affirmed that play-based activities encourage learning in pivotal academic subject areas such as Literacy and Mathematics. Parker et al (2022) and Lunga et al (2022) affirm that young learners learn from their peers while they play, and these authors argue that it is during such activities that they integrate their language, customs and culture through play activities.…”
Section: Background To the Studymentioning
confidence: 99%
“…Vygotsky's social development theory argues that utilising play in early childhood development creates a ZPD where young learners can learn from their peers. Other studies that were reviewed, such as those by Bodrova and Leong (2003), Johnson, Christie and Wardle (2005), Murtagh and Sawalma (2020) and Lunga et al (2022), demonstrated the importance of play in early childhood development. Conversely, this study indicated that the rural teachers under study found it very challenging to implement play effectively in Grade 3.…”
Section: Specific Theme-based Findings Theme 1: Language Developmentmentioning
confidence: 99%
“…The random effects model results showed a positive effect. In addition, Murtagh et al (2022) explored the relationship between play-based learning and achievement in mathematics in Palestinian elementary school children. Forty teachers from eight schools received training in play-based pedagogies and follow-up support visits from programme staff, four matched schools served as the control group.…”
Section: Empirical Literaturementioning
confidence: 99%